PERLINDUNGAN HUKUM BAGI PERUSAHAAN ASURANSI ATAS TERTANGGUNG YANG MELANGGAR HAK SUBROGASI - Marsidah, Marsidah (Solusi, 2017)
Insurance plays an important role in providing protection for people who are commercial and non-commercial. The problems studied are; How does the insurance company protect against the insured that violates the right of subrogation. The type of research used is the type of normative legal research, namely research conducted on written regulations relating to the issue of subrogation rights in insurance under the provisions of Article 284 legal code of law (KUHD) and standard agreements / standard clauses. Legal protection against insurers on the insured who violate the right of subrogation is to claim compensation against the insurer and the third party that the insurer or the insurer can claim back to the insured at any time as long as true proven